Associations between maternal socioeconomic position and psoriasis: a cohort study among the offspring of the Danish National Birth Cohort. (1st February 2019) - Groot, J.; Nybo Andersen, A.M.; Adam, A.; Tind Nielsen, T.E.; Blegvad, C.; Skov, L.
Summary: Background: The socioeconomic determinants of paediatric‐onset psoriasis have not been previously investigated. Objective: To identify whether a social gradient exists for paediatric‐onset psoriasis, using measures of maternal socioeconomic position. Methods: Data on paediatric‐onset psoriasis from 36 003 Danish National Birth Cohort offspring were cross‐linked with nationwide registry data on maternal age and three measures of maternal socioeconomic position: maternal educational attainment, maternal labour market attachment and equivalized household income. Univariable and multivariable logistic regression analyses were conducted to estimate the odds ratios (ORs) of psoriasis in the offspring, in cohort analyses for data from the year of enrolment and cross‐sectional analyses from the year of the 11‐year follow‐up. Results: Maternal age at birth, maternal educational attainment and equivalized household income were inversely associated with psoriasis in the offspring. Low maternal educational attainment was associated with offspring psoriasis [adjusted OR 1·62, 95% confidence interval (CI) 1·20–2·18] after adjusting for maternal psoriasis and age in the cohort analysis. The crude OR of psoriasis in offspring of mothers in the highest quartile compared with mothers in the lowest quartile of equivalized household income was 0·57 (95% CI 0·43–0·76), and the adjusted OR was 0·59 (95% CI 0·44–0·80) after adjusting for maternal psoriasis and age. Similar results were observed for data on maternal socioeconomic position at enrolment and at follow‐up. Conclusions: A steep social gradient in paediatric‐onset psoriasis was observed. Maternal socioeconomic position may play a role in early‐life exposure to modifiable risk factors for psoriasis. Future studies may help to elucidate which biological factors mediate the social gradient observed in our study.